Nonmotor Symptoms in Patients with PARK2 Mutations - Asako Yoritaka; Yumi Shimo; Yasushi Shimo; Yuichi Inoue; Hiroyo Yoshino; Nobutaka Hattori (Parkinson's Disease)
Decreased 123I-meta-iodobenzylguanidine (MIBG) uptake in MIBG myocardial scintigraphy, olfactory dysfunction, and rapid eye movement (REM) sleep behavior disorder (RBD) are considered useful early indicators of Parkinson disease. We investigated whether patients with PARK2 mutations exhibited myocardial sympathetic abnormalities using MIBG scintigraphy, olfactory dysfunction using the Sniffin’ Sticks olfactory test, and RBD using polysomnography. None of the examined patients had RBD, and all except 1 patient exhibited an increase in the olfactory threshold. Moreover, one of the oldest patients exhibited impairment in identification and discrimination. Of 12 patients with PARK2 mutations, 4 patients, who were older than patients without abnormal uptake, exhibited decreased MIBG uptake. The results obtained in this study suggest that some patients with PARK2 mutations have increased thresholds of olfactory function and myocardial sympathetic dysfunction as nonmotor symptoms.